2022
DOI: 10.3390/medicina58010084
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Future Therapeutic Options for Fecal Microbiota Transplantation

Abstract: The intestinal microbiota plays an important role in maintaining human health, and its alteration is now associated with the development of various gastrointestinal (ulcerative colitis, irritable bowel syndrome, constipation, etc.) and extraintestinal diseases, such as cancer, metabolic syndrome, neuropsychiatric diseases. In this context, it is not surprising that gut microbiota modification methods may constitute a therapy whose potential has not yet been fully investigated. In this regard, the most interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 163 publications
0
18
0
1
Order By: Relevance
“…In most patients with IBS, gut microbiota diversity is reduced, an increase of Enterobacteria is exhibited alongside a comparatively reduced quantity of Bifidobacteria and Lactobacilli , and the ratios of the main gut microbiota phylotypes are upset ( 28 ). Since gut dysbiosis is currently considered an important pathogenetic factor of IBS, various therapeutic strategies associated with gut microbiota modification (including FMT) have recently been the subject of intensive study ( 19 ). There are several prospective and RCTs of FMT’s effectiveness in IBS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most patients with IBS, gut microbiota diversity is reduced, an increase of Enterobacteria is exhibited alongside a comparatively reduced quantity of Bifidobacteria and Lactobacilli , and the ratios of the main gut microbiota phylotypes are upset ( 28 ). Since gut dysbiosis is currently considered an important pathogenetic factor of IBS, various therapeutic strategies associated with gut microbiota modification (including FMT) have recently been the subject of intensive study ( 19 ). There are several prospective and RCTs of FMT’s effectiveness in IBS.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that PI-IBS is brought on by infection and gut microbiota may be associated with the onset of symptoms, the modification of altered gut microbiota with non-absorbable antibiotics such as rifaximin-α or probiotics is often employed as first-stage treatment ( 17 , 18 ). Research in recent years has also shown the potential benefits of fecal microbiota transplantation (FMT) for IBS, which is the replacement of a sick recipient’s gut microbiota with fecal material from a healthy donor ( 19 , 20 ). Even though the only officially approved indication for FMT at this time is recurrent Clostridium difficile infection, the effectiveness of FMT is nevertheless being studied for treating other gastrointestinal and non-gastrointestinal pathologies, including IBS ( 19 , 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms proposed to participate in colorectal carcinogenesis are the alteration of the intestinal epithelial barrier, the production of genotoxins and the secretion of toxic metabolites by pathogenic bacteria [ 63 ]. Herbert et al introduced the idea that microbial interventions could be beneficial in CRC, and although there are studies where it seems to be a plausible method to increase anti-tumor effects, there is still an urgent need to clarify its benefit in clinical models and daily practice [ 64 , 65 ].…”
Section: Gut Microbiome and Cancermentioning
confidence: 99%
“…Несмотря на наличие многочисленных нерешённых проблем [13], существует немало публикаций, где описываются связанные с ней технические и организационные вопросы [14,15]. Предполагается, что в основе эффективности ТФМ лежит создание в кишечнике конкурентной среды за счёт непатогенных микроорганизмов и выработки ими антимикробных веществ, таких как бактериоцины.…”
Section: Introductionunclassified